Pengaruh Pendidikan Terhadap Tingkat Kemiskinan Dan Pengangguran Di Provinsi Aceh - Adela; Andiny, Puti; Asnidar (Shofanah Media Berkah, 2024)
This research aims to investigate the influence of education on poverty and unemployment in Aceh within the timeframe of 2013-2022. The method employed is time series data analysis using path analysis. The results indicate that education has a direct, negative, and significant impact on the poverty rate, as well as a direct, negative, and significant impact on the unemployment rate. Additionally, it is found that poverty has a direct, positive impact on unemployment, albeit not significant. Indirectly, education also exerts a significant influence on the unemployment rate through the poverty variable. The total coefficient of determination in thus study is 99,44%, while the remaining 0,03% is influenced by other variables such as per capita income, labor force participation rate, and others.